A Counselor Education Case Study: The Counselor Values‐Based Conflict Model in Action. Issue 2 (7th October 2018) - Grunhaus, Colleen M. L.; Tuazon, Victor E.; Gonzalez, Edith; Wagner, Nathaniel J.
Abstract : This article is based on the 2nd‐place winning entry to the 2016–2017 American Counseling Association Graduate Student Ethics Competition and includes a fictional case study of a counselor trainee whose personal beliefs conflict with her client's goals, and of her doctoral supervisor who is reticent to seek consultation. The counselor values‐based conflict model (Kocet & Herlihy, 2014 ) is used to generate an ethical resolution for the dilemma. Implications for counselors, supervisors, and counselor educators are discussed.